High Blood Pressure prevention and control: from evidence to action (Colombia Medica, 2018)
The Pan American Health Organization (PAHO) with the World Hypertension League has established the 17th May to promote the prevention and control of High Blood Pressure (HBP). Currently nearly 1.13 billion of adults suffer from HBP (blood pressure ≥140/90 mm Hg) worldwide. While HBP prevalence decreased in high income countries (HIC) between 1975 and 2015, the opposite trend was observed in low- and middle- income countries (LMIC). Particularly, in Latin American and Caribbean countries the prevalence decreased from 40.6% to 26.8% and from 26.8% to 19.4% for men and women between 45 to 49 years old respectively. However, in 2015, HBP accounted for 8.9 of the total of disability adjusted life years (DALYS) and was associated with 4.9 million, 2.0 million and 1.5 million deaths due to ischemic heart disease, hemorrhagic stroke and ischemic stroke respectively. Therefore, HBP is the leading cardiovascular risk factor worldwide. In Colombia, the last National Health Survey reported a global prevalence of 22.8% and nearly 60% for those between 60 and 69 years in 2007